Assessing Visitor Satisfaction and Its Determinants: An Empirical Analysis of Tourists at Chobhar - Gautam, Mandira; Niraula, Damodar (The Batuk, 2025)
This study assessed the determinants influencing visitor satisfaction in Chobhar, a developing tourist destination located on the outskirts of Kathmandu, Nepal. The research focused on five key independent variables- environment, society, service quality, cost, and accessibility to explore their effect on overall tourist satisfaction. A quantitative research design was employed, targeting tourists visiting Chobhar as the study population. Primary data were collected through a structured close-ended questionnaire administered to 85 respondents selected via convenience sampling. The data were analyzed using descriptive statistics, correlation, and linear regression with the help of Jamovi software. The findings revealed that accessibility and cost had statistically significant and positive effect on visitor satisfaction, suggesting that ease of access plays a critical role in shaping positive tourist experiences. The result showed positive but non-significant effect of society on tourist satisfaction. In contrast, environment and service quality exhibited a minimal and non-significant effect on tourist satisfaction. These findings suggest that not all commonly assumed determinants have the same effect on visitor satisfaction. The study offers practical implications for tourism planners and local stakeholders aiming to enhance satisfaction and sustain tourism growth in Chobhar.